Immunomodulatory agents for COVID-19 treatment: possible mechanism of action and immunopathology features - Rommasi, Foad; Nasiri, Mohammad Javad; Mirsaeidi, Mehdi (Molecular and cellular biochemistry, 2022)
The novel coronavirus pandemic has emerged as one of the significant medical-health challenges of the current century. The World Health Organization has named this new virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since the first detection of SARS-CoV-2 in November 2019 in Wuhan, China, physicians, researchers, and others have made it their top priority to find drugs and cures that can effectively treat patients and reduce mortality rates. The symptoms of Coronavirus Disease 2019 (COVID-19) include fever, dry cough, body aches, and anosmia. Various therapeutic compounds have been investigated and applied to mitigate the symptoms in COVID-19 patients and cure the disease. Degenerative virus analyses of the infection incidence and COVID-19 have demonstrated that SARS-CoV-2 penetrates the pulmonary alveoli's endothelial cells through Angiotensin-Converting Enzyme 2 (ACE2) receptors on the membrane, stimulates various signaling pathways and causes excessive secretion of cytokines. The continuous triggering of the innate and acquired immune system, as well as the overproduction of pro-inflammatory factors, cause a severe condition in the COVID-19 patients, which is called "cytokine storm". It can lead to acute respiratory distress syndrome (ARDS) in critical patients. Severe and critical COVID-19 cases demand oxygen therapy and mechanical ventilator support. Various drugs, including immunomodulatory and immunosuppressive agents (e.g., monoclonal antibodies (mAbs) and interleukin antagonists) have been utilized in clinical trials. However, the studies and clinical trials have documented diverging findings, which seem to be due to the differences in these drugs' possible mechanisms of action. These drugs' mechanism of action generally includes suppressing or modulating the immune system, preventing the development of cytokine storm via various signaling pathways, and enhancing the blood vessels' diameter in the lungs. In this review article, multiple medications from different drug families are discussed, and their possible mechanisms of action are also described.